2017
DOI: 10.1159/000479030
|View full text |Cite
|
Sign up to set email alerts
|

Remission Phase in Paediatric Type 1 Diabetes: New Understanding and Emerging Biomarkers

Abstract: Type 1 diabetes (T1D) is a metabolic disease of unknown aetiology that results from the autoimmune destruction of the β-cells. Clinical onset with classic hyperglycaemic symptoms occurs much more frequently in children and young adults, when less than 30% of β-cells remain. Exogenous insulin administration is the only treatment for patients. However, due to glucose dysregulation, severe complications develop gradually. Recently, an increase in T1D incidence has been reported worldwide, especially in children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
58
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 54 publications
3
58
1
3
Order By: Relevance
“…Second, we revealed that although there was no difference in DKA prevalence between patients with and without PR, remitters had significantly higher first measured blood pH at T1D onset, and it was the most important predictor of PR occurrence. These results partially confirm the observations of other authors that children with DKA at first hospital admission are less probable to enter PR . It may be postulated that patients with higher pH were in a better clinical condition—probably because the amount or functional capacity of remaining beta cell was in these individuals higher at diagnosis.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Second, we revealed that although there was no difference in DKA prevalence between patients with and without PR, remitters had significantly higher first measured blood pH at T1D onset, and it was the most important predictor of PR occurrence. These results partially confirm the observations of other authors that children with DKA at first hospital admission are less probable to enter PR . It may be postulated that patients with higher pH were in a better clinical condition—probably because the amount or functional capacity of remaining beta cell was in these individuals higher at diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, also in a cohort of adolescents with T1D an autologous non‐myeloablative hematopoietic stem cell transplantation was more effective in patients without DKA at diagnosis . In this study, we proved additionally that with rising pH values the duration of PR increased; however, results from other cohorts are not unequivocal …”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations